Extended Spectrum Beta Lactamase Escherichia Coli in Bagmati River, Kathmandu Valley - Ghimire, Bindu; Pokherel, Muna Kumari; Banjara, Megha Raj; Rijal, Komal Raj; Ghimire, Prakash (Journal of Nepal Health Research Council, 2024)
Background: Antimicrobial resistance organisms in the peripheral communities of an environment can be predicted by the presence of extended-spectrum beta-lactamase Escherichia coli in that environment. The close connectivity between humans and water sources can facilitate the entry of antimicrobial resistant organisms into the human ecosystem. The aim of this study was to assess beta lactamase producing Escherichia coli from Bagmati river within Kathmandu valley. Methods: In the year 2020, a cross-sectional study was conducted on water samples collected from 66 locations along the Bagmati River. Coliforms were isolated by five tubes dilution method and identified by cultural and biochemical tests. Further Escherichia coli was isolated in eosin methylene blue agar at 44.5 ?C. Antibiotic susceptibility test was performed by Kirby Bauer disk diffusion methods. Beta lactamase gene types were detected by using conventional multiplex polymerase chain reaction. Results: A total of 615 bacterial isolates were identified among which 39 % (n=241) were Escherichia coli. Extended spectrum beta lactamase producing Escherichia coli was confirmed in 16.6 % (40/241) of total Escherichia coli isolates. Among 66 sites this isolate was detected in 26 (40 %) sampling sites excluding upstream regions. All the Escherichia coli isolates were multidrug resistance showing higher percentage (>99 %) of resistant for penicillin, tetracycline and erythromycin antibiotics. There were significant differences in resistance rate for cefotaxime and ceftazidime by extended spectrum beta lactamase producing and non-producing Escherichia coli (p<0.05). Conclusions: Presence of multidrug resistance extended spectrum beta lactamase producing Escherichia coli in river streams suggests the chances of circulating within river system and hence transmitting in human community. Key words: Bagmati river; drug resistance; escherichia coli; human.